Addressing human error when collecting failure cause information in the oil and gas industry: A review of ISO 14224:2016. (February 2020) - Selvik, Jon T.; Bellamy, Linda J.
Highlights: The ISO 14224:2016 has a higher focus on human errors compared with 2006 edition. The terms 'error' and 'human error' is linked in an appropriate way. Sound expandable basis for understanding human error influence on equipment failure. Abstract: The international standard ISO 14224 provides key guidance on how to achieve quality information about equipment failures for decision-making in the oil and gas industry, including specific guidance on data collection concepts and how to record and categorize failure causes. The third edition, issued in September 2016, is still focusing mainly on equipment failures, but has a higher focus on human errors than previously. It provides a 'human error' definition, currently the only one in an ISO standard, and a link to several types of error used in failure cause classification. In this article, the authors study the value of this added focus on human errors by assessing the definition and effect on failure cause classification, discussing the benefits and challenges. It is concluded that the standard has provided a clear distinction between the terms 'error' and 'human error' while being consistent in the use of the term 'error'. However, it gives limited guidance on how to separate and collect different types of human error, such as mistakes, slips and lapses, making this largely an interpretation issue. Nevertheless, applying ISO 14224 will provide data for learning about the role of human error in equipment failure on a sound expandable basis.